Typhus epidemic in Kuibyshev during the Great Patriotic War - O. Yu. Igoshina (Омский научный вестник: Серия "Общество. История. Современность")
The author studies the problem of the spread of typhus epidemic in the Kuibyshev (Samara) region during the Great Patriotic War. The author analyzes the causes, features and dynamics of diseases in this article, as well as measures that were aimed at overcoming infection. It is revealed that the causes of the epidemic included a huge increase of the urban population, a decrease in the complex of sanitary and living conditions, complicated by the collapse of the health system in the rear. It is found that in a few months the number of cases increased in 15 times. Dangerous infection became one of the factors of super-mortality of the population in the region. The epidemic spread to the population of all ages. Renovation of the health system, strict sanitary control, improvement of living conditions of the population, as well as sanitary and educational work were able to stop the infection and prevent it from entering the front